ANALISA PENGARUH VARIASI MEDIA PENDINGIN DAN WAKTU AGING PADA PERLAKUAN PANAS T6 TERHADAP STRUKTUR MIKRO KOMPOSIT ALUMINIUM ABU DASAR BATUBARA - Susanto, Juli; Seputro, Harjo; Santoso, Edi (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2016)
Â Aluminium is a metal which has a mild nature, corrosion resistance, and electrical conductors that are used as matiks. Bottom ash coal used for reinforcement which is useful for producing aluminum composite with excellent mechanical properties and low cost. Besides the mechanical properties of aluminum can be enhanced by the addition of alloying elements (alloying) and the heat treatment process (heat tretment). The purpose of research is a comparative changes in microstructure before and after T6 heat treatment. This research will look at the changes in the microstructure of aluminum composite bottom ash coal that have undergone a process of T6 heat treatment that includes, (solid solution) is done at a temperature of 540 Â°C with a holding time of 6 hours, (quenching) with media cooling water, salt water (brine), oil, and (aging) with aging time of 2 hours, 4 hours, and 6 hours at a temperature of 180 Â°C From the results of tests performed on the aluminum composite material coal bottom ash, before and after T6 heat treatment process shows that. Granules greatest average diameter of the grain is shown by the media granules with salt water cooling 6-hour holding time for 165,3pm, and the smallest is 95,58pm with water cooling media holding time 6 hours, while aluminum composite granules of coal bottom ash without treatment equal to 158.4 pmKeywords: aluminum, coal bottom ash, heat treatment, quenching, aging, microstructure